Post “APecR” on self - health profiling among aged 50’s individuals: case study / Chee Hian Tan … [et al.] - Chee, Hian Tan; Jung, Young Lee; Raja Azidin, Raja Mohammad Firhad; Walter King, Yan Ho (Universiti Teknologi MARA, 2023)
Introduction: APecR was a self – health profiling program with natural physical activity which came to one APecR = 138 Kcl burnt and was registered as one measured unit or patterned (LY2019004970- 28/8/19). Method: Field experimental to justify the effectiveness of APecR as profiling tool. 21 participants voluntarily as they were from previous study with continuity another 3 cycles (3 months’ time, same year). Results: Lifestyle which was categorized as Very Active (> 12,000 steps) = 10.2%, Active (> 10,000 steps) = 43.7%, Moderate (7,500 - 9,999 steps) = 37%, Not Active (50000 – 7499 steps) = 10.0% and without Sedentary lifestyle (< 5,000 steps) after the eventual APecR. Overall mean steps and Kilocalories burnt liked: October - 12,161 steps, and burn with 3.8 APecR (524.4Kcl), November - 13,197 steps, burned with 3.5 APecR (483Kcl) and December with average steps - 12, 005, and burn up to 5.3 APecR (731.4Kcl). Sleeping pattern showed on bed time was prolong from 7 hours 6 second (October) to 7 hours and 16 minutes (December). Weight Lose and Heart Rate: October with weight 81.5Kg, BP reading Excel = 120/80 - 31%, Normal = 130/85- 35%, Normal Systolic = 140/90- 32% and Mild Hyper (2%). In December weight scale slightly dropped to 80.3Kg and blood pressure with Excel (34%), Normal (45%), Normal Systolic = 19% and Mild = 2%. Conclusion: ApecR contributed to practices, delivering fitness towrads health knowledge and post effect of APecR as unit measured and technique proven as an enhancing maintenance domain.